2013
DOI: 10.1016/j.jfluidstructs.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Low speed flutter and limit cycle oscillations of a two-degree-of-freedom flat plate in a wind tunnel

Abstract: Amandolese, X., et al., Low speed flutter and limit cycle oscillations of a two-degree-offreedom flat plate in a wind tunnel. Journal of Fluids and Structures (2013) ABSTRACTThis paper explores the dynamical response of a two-degree-of-freedom flat plate undergoing classical coupled-mode flutter in a wind tunnel. Tests are performed at low Reynolds number (Re ~ 2.5×10 4 ), using an aeroelastic set-up that enables high amplitude pitch-plunge motion.Starting from rest and increasing the flow velocity, an unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 22 publications
9
40
0
Order By: Relevance
“…The value of π=2, predicted by the thin-airfoil theory is plotted with a black solid line. The present results compare well with previouslyreported data of Fage and Johansen (1927), Pelletier and Mueller (2000), and Amandolese et al (2013). A careful and highresolution measurement of the pitching moment at fixed angles is shown in Fig.…”
Section: Static Aerodynamic Momentsupporting
confidence: 93%
See 1 more Smart Citation
“…The value of π=2, predicted by the thin-airfoil theory is plotted with a black solid line. The present results compare well with previouslyreported data of Fage and Johansen (1927), Pelletier and Mueller (2000), and Amandolese et al (2013). A careful and highresolution measurement of the pitching moment at fixed angles is shown in Fig.…”
Section: Static Aerodynamic Momentsupporting
confidence: 93%
“…Our current ability to model large-amplitude oscillations due to fluid-structure instabilities remains insufficient, albeit a number of experimental studies reported in the archival literature (e.g., Dimitriadis and Li, 2009;Razak et al, 2011;Amandolese et al, 2013). Significant efforts have been made to elucidate the mechanism by which a classical linear flutter transforms into a complex bifurcation behavior that leads to violent oscillations induced by the dynamic stall phenomenon.…”
mentioning
confidence: 99%
“…These preliminary findings will be confronted to experiments in order to confirm the potential of the SMA as a passive device for controlling the flutter instability. Preliminary results with aeroelastic parameters fitted to the experiments reported in [9] show an important increase of Θ c so that the LCO amplitudes should be controlled on a larger range of flow velocities.…”
Section: Resultsmentioning
confidence: 86%
“…Also the decreasing trend with the increasing velocities has been pointed out by authors like Amandolese or Matsumoto [155,158,159]. According to this last reference, the plate is suffering a high-speed torsional flutter.…”
Section: Frequency Evolutionmentioning
confidence: 71%
“…Caracoglia presents some of the proposed apparatuses and introduces a new one in [154]. Therefore, it is clear that this investigation line is far from being over, and many researchers work on it [147,150,155].…”
Section: Catenary Flow Conditionmentioning
confidence: 99%